(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The majority of economic, commercial, cultural, social, and governmental activities andcontacts of nations are now conducted in cyberspace at all levels, including people, non-governmentalgroups, and government and governmental institutions. Cyber-attacks and the hazards of wirelesscommunication technologies are now a concern for many business organisations and governmentbodies throughout the world. In today’s society, which is largely dependent on electronic technology,protecting data from cyber-attacks is a challenging undertaking. Businesses suffer financial losses as aresult of cyber-attacks. In some circumstances, cyber-attacks might be utilised for military or politicalpurposes. PC viruses, knowledge breaks (DDS), and other attack vectors are examples of thesedamages. To achieve this purpose, a range of tactics for mitigating the impact of cyber-attacks are usedby many firms. Cyber security is built on the most up-to-date IT data in real time.Until date, scholarsfrom across the world have proposed a range of strategies for avoiding cyber-attacks or minimising thedamage they do. Some of the methods are now in use, while others are still under investigation. Thepurpose of this study is to look at the challenges, weaknesses, and strengths of the various techniquesas well as to evaluate the current state of cyber security.